An unusual case of bilateral peroneal palsies due to fabellae. (28th February 2017) - Décard, Bernhard F.; Nagy, Sara; Garcia, Meritxell; Fuhr, Peter
Abstract : A 28-year-old otherwise healthy man presented twice with a peroneal nerve palsy, first on the left and 4 months later on the right side. Both palsies occurred after sitting on a chair for a few hours. Personal and family history were unremarkable. Electrophysiologic examinations revealed conduction blocks of the peroneal nerves slightly above the fibular head and signs of acute denervation in the anterior tibial muscles. Bilateral fabellas (sesamoid bones) within the tendon of the lateral head of gastrocnemius muscles detected by ultrasound and MRI (figure) caused these unusual pressure palsies. 1 Surgical excision of the fabellae resulted in full recovery.